Improving Distress and Behaviors for Parents of Adolescents With Chronic Pain Enrolled in an Intensive Interdisciplinary Pain Program. Issue 9 (September 2019) - Weiss, Karen E.; Junghans-Rutelonis, Ashley N.; Aaron, Rachel V.; Harbeck-Weber, Cynthia; McTate, Emily; Luedtke, Connie; Bruce, Barbara K.
Abstract : Objectives: Intensive interdisciplinary treatment is emerging as an effective treatment of chronic pain in youth. These programs often include a parental component with the belief that targeting parental distress and responses to a child's pain will improve outcomes. However, few studies have evaluated the impact of a parental intervention in the interdisciplinary treatment of pediatric chronic pain. The present study consists of a nonrandomized pre-post design to evaluate change in psychological and behavioral functioning of parents who participated in intensive parent programming that utilized cognitive-behavioral therapy and acceptance and commitment therapy, delivered within the context of an interdisciplinary intensive 3-week pain treatment program for youth with chronic pain. Materials and Methods: Two hundred twelve parents and their children participated in the study, with 116 participants completing 3-month follow-up measures. Parents completed measures of depressive symptoms, pain catastrophizing, protective responses, and psychological flexibility at admission, discharge, and 3 months after the program. Child functional disability was assessed at the same time points. We examined change in parent factors over time, while controlling for change in child distress. Results: Parents reported significant improvements in all areas of functioning from admission to discharge and improvements were maintained at 3-month follow-up. Discussion: This study provides evidence suggesting parent interventions can be effective in reducing parent distress and behaviors known to be associated with child outcomes.